2017
DOI: 10.1177/0143831x17734297
|View full text |Cite
|
Sign up to set email alerts
|

Insecurity in the Ivory Tower: Direct and indirect effects of pay stagnation and job insecurity on faculty performance

Abstract: Despite unprecedented cuts to public funding of state universities, little research has examined economic stressors in academia. This study addresses this gap in research by examining the direct and indirect relationships of pay stagnation and job insecurity to performance among a sample of 355 faculty members from a public university in the United States undergoing major budget cuts. In line with job stress and psychological contract breach theories, among tenured faculty, both job insecurity and pay stagnati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 46 publications
2
20
0
Order By: Relevance
“…Job insecurity reflects anticipation of a potential change in employment status (De Witte, 1999; Shoss, 2017), and its relationship with emotional strain is well established (De Cuyper, Bernhard-Oettel, Berntson, De Witte, & Alarco, 2008; De Witte et al, 2010). Job insecurity researchers frame job insecurity as a threat to future resources and frequently use COR theory to explain job insecurity’s effects (Benson et al, 2017; Cheng, Mauno, & Lee, 2014; De Cuyper, Mäkikangas, Kinnunen, Mauno, & Witte, 2012; Jiang & Probst, 2014, 2017; Ünal-Karagüven, 2009). Particularly relevant to the current study, Shoss, Brummel, Probst, and Jiang (2020) recently used COR to argue that job insecurity and job satisfaction interact to shape a variety of outcomes, suggesting that people’s anticipated change in job status may shape how they respond to their current job conditions.…”
Section: Cor Theory and Anticipated Workload Changementioning
confidence: 99%
“…Job insecurity reflects anticipation of a potential change in employment status (De Witte, 1999; Shoss, 2017), and its relationship with emotional strain is well established (De Cuyper, Bernhard-Oettel, Berntson, De Witte, & Alarco, 2008; De Witte et al, 2010). Job insecurity researchers frame job insecurity as a threat to future resources and frequently use COR theory to explain job insecurity’s effects (Benson et al, 2017; Cheng, Mauno, & Lee, 2014; De Cuyper, Mäkikangas, Kinnunen, Mauno, & Witte, 2012; Jiang & Probst, 2014, 2017; Ünal-Karagüven, 2009). Particularly relevant to the current study, Shoss, Brummel, Probst, and Jiang (2020) recently used COR to argue that job insecurity and job satisfaction interact to shape a variety of outcomes, suggesting that people’s anticipated change in job status may shape how they respond to their current job conditions.…”
Section: Cor Theory and Anticipated Workload Changementioning
confidence: 99%
“…Apart from the "tenured" and its opposite concept -"non-tenured" (Benson, Probst, Jiang, Olson, & Graso, 2020), which is quite widely used in the academic circles, to demonstrate the complex inherent academic culture and speak of highly diverse national, regional, institutional labour policy intensive context, the academic community applies a wide range of distinctions -"part-time (part-timers), adjunct" (Xu, 2019), "casual" (Narayan, 2020), "sessional staff" (Broadbent, 2018;Harvey, & Jones, 2020), to denote a non-permanent staff member in higher education from the core personnel.…”
Section: Methodsmentioning
confidence: 99%
“…This is critical to note as it is documented that wage growth around 4% is necessary for employees to actualize the benefits of macro-economic growth, such as increased disposable income [ 123 ]. Under this threshold, it becomes difficult for employees to regain the wage resources necessary to help them bounce back from financial challenges experienced during a recession [ 124 ]. This lack of financial realization is detrimental when considering the host of negative well-being effects associated with constant worry over financial security and debt [ 125 , 126 ].…”
Section: Compensation and Benefitsmentioning
confidence: 99%
“…Occupational safety and health researchers have highlighted pay inequality as a grand challenge for future research and demonstrated its link to negative well-being outcomes [ 129 , 157 ]. Research on strategies to support employee wage growth and mitigate inequality would be beneficial in reducing economic stress of employees and associated negative health outcomes [ 124 ]. Similarly, a better understanding of the nuances surrounding income redistribution policies is necessary to help employees financially cope and rebound from the burdens placed on them during the pandemic [ 158 , 159 ].…”
Section: Compensation and Benefitsmentioning
confidence: 99%